Perbedaan Peningkatan Berat Badan Bayi Usia 6 Bulan Antara Bayi yang Mendapat ASI Eksklusif dan Susu Formula Di Wilayah Kerja Puskesmas Kartasura - dewi, noermawati (2016)
ABSTRACT THE DIFFERENCE OF WEIGHT GAIN IN 6 MONTHS OLD INFANTS WHO RECEIVED EXCLUSIVE BREASTFEEDING AND FORMULA FEEDING IN THE WORK AREA OF HEALTH CENTER KARTASURA NoermawatiDewi, Rusmawati, N. JuniTriastuti Medical Faculty of Muhammadiyah Surakarta University Background:Anthropometric measurement such as weight gain is important in the infant's examination to measure the nutritional status. Increasing of infant's weight gain can be influenced by various factors such as genetics, sex, nutrition, parenting, including feeding. Exclusive breastfeeding provides suficient nutrition and prevent the infant from overweight. On the contrary, formula feeding in infants less than 6 months old can be a high-risk babies overweight. Objective: This study aimed at analyzing the difference of weight gain in 6 months old infants who received exclusive breastfeeding and formula feeding in the work area of health center Kartasura. Methods: This study used an observational analytic method with cross sectional approach, using cluster random sampling, which was done to 66 infants aged ≥ 6 months from 12 Posyandu in the region of Kartasura health center. Dataobtained from questionnaire and KartuMenujuSehat (KMS) and were analyzed by using Mann Whitney test. Results: Mean of weight gain per month of infants who were exclusively breastfed was 633 grams, lower than formula fed infants, that was 775 grams. Based on the result of Mann Whitney test to determine difference in weight gain between infants who receive exclusively breasfeeding and formula feeding, p value <0,005. Conclusions: Weight gain in infants who were exclusively breastfeeding was lower than formula-fed infants. Keywords: weight gain, exclusive breastfeeding, formula feeding